PENGGUNAAN REGISTER DALAM BISNIS DIGITAL MERCHANDISE K-POP DI MEDIA SOSIAL TWITTER - Zahrra Oktavia Savitri G. (Politeknik Negeri Jakarta, 2023)
The Korean Wave or the Korean Cultural Wave is a term used to describe the rapid spread and popularity of Korean culture and entertainment. Pop music called K-Pop is one of the Korean Wave products that is in great demand by millennials. K-Popers often use certain terms or registers when making buying and selling transactions in digital business, especially on social media Twitter. The variety of registers that are emerging in Indonesia is currently increasing rapidly in all areas of the digital business world. Some register features appear as unique new language forms or distinctive characteristics. The purpose of this study is to find out the forms of registers that appear in the K-Pop digital merchandise business, and to find out the impact of using these registers on Indonesian or native languages. The method used in this study is a qualitative descriptive approach with document data collection techniques. While the data analysis technique used is content analysis technique. The results of the study show that there are several languages in the register used by K-Popers, including Indonesian, English and Korean. These registers are categorized into four characteristics, namely (1) characteristics of the acronym form register, (2) changes in meaning, (3) single, and (4) complex. The researcher found a code switching phenomenon at the word level. Some of the registers used are a combination of English and Indonesian. English seems to be more mastered or dominating than Indonesian and Korean. This shows that Indonesian is weaker because it is not used massively. This phenomenon seems to be taken for granted by K-Pop fans, even though this is not the native language that is usually used in daily activities. The researcher did not find any characteristics of a positive attitude towards language, namely language loyalty, language pride, awareness of language norms.